Evaluation of Differentiated Learning in Chemistry by Using the CIPP Evaluation Model - Sukro Muhab; Tatik Dian Setyo Rini; Erdawati Erdawati; Irwanto Irwanto (Postgraduate, University of Mataram, 2024)
Differentiated learning is important in the world of education, because of the diversity of students’ learning methods and students’ different knowledge backgrounds. The aim of this research is that differentiated learning in chemistry material and the teaching and learning process can run effectively and efficiently. Differentiated learning can eliminate students’ fear of material they don’t like, especially chemistry. This research is qualitative research, to see the effectiveness of differentiated learning, the CIPP research model is used. This CIPP model includes context, input, process and product, so it is said to be more comprehensive than other evaluation models. The research data sources are Chemistry Teachers, curriculum representatives, and students at three high schools in Jakarta. Primary data was collected using observation instruments while secondary data was obtained through questionnaires and interviews. The research results show that what happens in the field is that not all teachers apply differentiated learning during the teaching and learning process in the classroom. Through differentiated learning, students tend to be more active and enthusiastic about learning because classroom learning is carried out according to each student’s interests, readiness, and learning style. So, learning activities with a differentiation system are stated to be quite effective